Immunogenicity and protection-inducing ability of recombinant Plasmodium vivax rhoptry-associated protein 2 in Aotus monkeys: A potential vaccine candidate (2009)
Rhoptry proteins have been extensively shown to be important in invasion and parasitophorous vacuole (PV) formation. This work evaluates the immunogenicity and protective efficacy of Plasmodium vivax RAP2 in the non-human Aotus primate model, when expressed as a recombinant molecule in E. coli and formulated in Freund and Alum hydroxide adjuvants. Our results show that rPvRAP2 is immunogenic in both formulations, finding a trend of higher cytokine levels in immunized monkeys, specially in IL-4 levels (using Freund's adjuvant) and IL-5 (using Alum hydroxide). RAP2 is suggested as a P. vivax-vaccine candidate since immunized monkeys exhibited lower parasitemias than control groups after being experimentally challenged with the P. vivax VCG-I strain. © 2009 Elsevier Ltd. All rights reserved.